Social Stigma in Adolescents Who Do Early Marriage at School Age - Diah Rahayu; Stefanny Ayu Danny; Novi Rizky Ramadhani; Alda Niarisma (International Journal of Social Science and Business, 2021)
Based on the results of a survey about teenage pregnancy of 7 adolescents aged 13-15 who were pregnant before marriage, who were still educated SLTP when pregnancy occurred. Early marriage is the most phenomenal symptom that often invites negative social stigma for society. Based on that, early marriage is an arranged marriage or marriage involving two parties between a man and a woman under the age of 18 years, which will usually give rise to negative stigma from the surrounding environment. Purpose of this study is to know people's views on early marriage and to know the level of social stigma against early marriage. Research method used in this research is qualitative research method, the approach used in this research is phenomenology. The study was conducted in Samarinda and several interviews were conducted in direct interaction with four subjects who had had early marriages in their teens or schools. The sampling technique used in this study is purposive sampling. The study subjects numbered 4 people. The results show factors that led to the subject of B.C. marrying young were due to parental and cultural factors. The factor that causes MAF subjects to have early marriage is the presence of pregnancy factors outside of marriage. RS gets a negative response from the surrounding environment and the factors that cause social stigma in subject RS. are the presence of knowledge and education. The reason AR married young are due to the parental factor.